The effect of perceived teacher support on self-regulated learning behaviors: language mindsets and L2 grit as chain mediators - Zhong, Shan; Wang, Zihao (Frontiers in Education, 2025)
The present study examines the complex relationships between perceived teacher support, language mindsets, L2 grit, and self-regulated learning behaviors among 522 students from five universities across China. The results showed that: (1) there are significant correlations between perceived teacher support, language mindsets, L2 grit, and self-regulated learning behaviors; (2) both growth language mindset and L2 grit are mediators in the relationship between perceived teacher support and self-regulated learning behaviors, and they also collectively serve chain mediators. However, the mediating effect of fixed language mindset is not significant. This study provides suggestions for promoting students’ self-regulated learning through shaping positive language mindsets and personalities, and offers an insight into further studies.